Current and near-term GHG emissions factors from electricity production for New York State and New York City. (1st February 2017) - Howard, B.; Waite, M.; Modi, V.
Highlights: A multi-regional unit commitment model was developed for New York State. The performance parameters of 191 generators were statistically estimated. Considered planned and proposed changes to the electricity system up to 2025. Average GHG emissions factors could reduce between 9% and 39% from 215 kg CO2 e/MWh. Marginal GHG emissions factors may reduce 30% from 540 kg CO2 e/MWh. Abstract: This paper reports estimates of average GHG emissions factors for New York State and marginal GHG emissions factors for interventions in New York City. A multi-regional unit commitment model was developed to simulate the behavior of the grid. The parameters defining the system operation were gathered from several publicly available data sources including historical hourly electricity production and fuel consumption from over one hundred power plants. Factors were estimated for a baseline year of 2011 and subsequently for the year 2025 considering planned power plant additions and retirements. Future scenarios are also developed considering different wind turbine installation growth rates and policies affecting the cost of generation from coal power plants. The work finds marginal GHG emissions factors for New York City could reduce between 30% and 36% from 540 kg CO2 e/MWh in 2011 for all future scenarios considered. Average GHG emissions factors for New York State could reduce 9–39% from 215 kg CO2 e/MWh depending on the wind growth rate and price burden on coal power plants.